The case study of Cascais municipality place branding based on Chinese tourist preferences - Yubai Wang (2022)
With the intensification of competition among tourist destinations in the market for source of tourists, the importance of tourist destination marketing to the development of tourism in various places has become increasingly prominent. The achievements of China's economic and social development in recent years have strongly promoted the expansion of the outbound tourism market. Despite the impact of the new crown pneumonia epidemic in 2020, Chinese national economy still maintains a strong resilience and a firm growth momentum, which shows that the economic support for the development of outbound tourism is still strong. Since the popularity of the Cascais tourist destination brand in the Chinese market is currently not high, in order to effectively develop the Cascais brand in the Chinese market in the future, the intention of this paper is to clarify the main directions that Cascais Municipality develops destination branding architecture through investigating the insight of Chinese outbound tourists who have intentions to visit Cascais. The study applied the qualitative and quantitative methodology to understand the portraits of the target segment and their preferences of Cascais destinations attributes, and a questionnaire was carried out on Weibo social platform.